Removal of zinc from wastewater by water hyacinth - Hasan S.H.; Rai S.; Rupainwar D.C. (My University, 2025)
The water hyacinth (Eichchornia crassipes) has been successfully utilized for the removal of Zn from simulated wastewater samples. It has been found that growth rate in general and relative growth rate in particular of the plant decreases with the increase of metal ion concentration. The process of metal uptake by the plant is monophasic in nature with the increase of metal ion concentration whereas it is biphasic in nature with the time of exposure. The rate of mobility of the metal is slow in the root than that for the top of the plants. However amount of metal accumulated in the root is larger as compared to the top of the plants. It has also been found that the percentage removal of the metal from the aqueous solution decreases with increasing initial concentration of the metal. The overall removal capacity of the plant has also been evaluated and found to fit the mathematical model. Thus the process can be recommended for the treatment of zinc-loaded wastewater.